(untitled) (The Macau Ricci Institute Journal, 2020)
The journey towards a new paradigm of economics must begin from a profound consideration of the inherent problems of existing models. Joseph Ratzinger argues that the market economy stresses freedom in order to produce efficient outcomes while the centralised economy emphasises regulation so as to produce ethical outcomes. A truly efficient and ethical economic model needs to be guided by an objective conception of the common good. Aristotle argues that rational economic activity should be oikonomia (household management) for the sake of attaining the welfare of the human being. He is opposed to the activity of chrematistike (wealth accumulation) which goes beyond what is necessary for human well-being and produces an unjust allocation of scarce resources. Chiara Lubich founded the Economy of Communion which presents a valuable alternative to the traditional distinction between profit-based enterprises and non-profit organisations. Entrepreneurs of this movement voluntarily commit to use profit to grow their own business, promote the “culture of giving” and assist others by means of social projects.